Study on promoting the regeneration of grafted fat by cell-assisted lipotransfer - Hongtao Fu; Shanshan Dong; Kun Li (Regenerative Therapy, 2023)
Background: Cell-assisted lipotransfer (CAL), a modified adipose-derived stromal/stem cells (ADSCs)-based approach for autologous fat grafting that is an ideal option for soft tissue augmentation, has many shortcomings in terms of retention and adverse effects. The objective of our study was to improve the treatment efficacy of CAL by adding fibroblasts. Methods: ADSCs and fibroblasts were isolated from human adipose and dermal tissues, with fibroblasts identified by immunofluorescence and ADSCs identified by the multilineage differentiation method. We performed cell proliferation, apoptosis, migration, adipogenic, and hemangioendothelial differentiation experiments, qPCR and Western blotting analysis in co-cultures of fibroblasts and ADSCs. Subsequently, we conducted animal experiments with BALB/c nude mice. Masson's staining, immunofluorescence staining and ultrasound were used to analyze the occurrence of adverse reactions of the grafted fat, and CT and three-dimensional reconstruction were used to accurately evaluate the volume of the grafted fat. Results: We found that the co-culture of fibroblasts and ADSCs promoted their mutual proliferation, adipogenic differentiation, hemangioendothelial differentiation and proliferation and migration of HUVECs. Fibroblasts inhibit the apoptosis of ADSCs. Moreover, in animal experiments, the autografted adipose group combined with ADSCs and fibroblasts had the least occurrence of oily cysts, and fat had the best form of survival. Conclusions: We enhanced adipocyte regeneration and angiogenesis in ADSCs and fibroblast cells after adding fibroblasts to conventional CAL autologous fat grafts. In turn, the volume retention rate of the grafted fat is improved, and the adverse reactions are reduced.